Optimization of Pharmacotherapy Within the Framework of a Patient-oriented Approach in the Treatment of Hypertension in Multimorbidity Patients (Clinical Case and Literature Review) - O. D. Ostroumova; I. A. Alyautdinova; S. N. Litvinova; A. V. Arablinskij; A. A. Kirichenko (Столичная издательская компания, 2021)
Arterial hypertension (AH) remains one of the main causes of disability and death worldwide, including in Russia. At the same time, the risks of coronary and cerebrovascular events increase in the presence of additional risk factors. The most common modifiable risk factors are metabolic disorders, including pre-diabetes, dyslipidemia, peripheral arterial atherosclerosis, and obesity, which also imposes certain features on the choice of optimal pharmacotherapy. Currently, the terminology of comorbid conditions continues to be discussed depending on their pathogenesis and the presence or absence of dominance of one disease over others, i.e. polymorbidity, comorbidity and multimorbidity. At the same time, "associative polymorbidity" is distinguished with a certain set of diseases that often occur in conjunction with each other with individual susceptibility of the body. One of the most common phenotypes of polymorbidity occurring in all age groups in both sexes is cardiometabolic, which is based on the formation of insulin resistance, sympathetic overactivity and chronic inflammation. This article provides a clinical example of the use of a fixed combination of angiotensin II receptor blocker telmisartan and calcium channel blocker amlodipine with the addition of an I1-imidazoline receptor agonist moxonidine in real clinical practice in a polymorbid cardiometabolic patient with target organ damage (left ventricular hypertrophy and microalbuminuria). High antihypertensive (favorable effect on 24-hour blood pressure, especially in the early morning) and organoprotective effectiveness of this combination, its possibilities in correcting additional risk factors (reduced heart rate, body weight and a positive effect on metabolic parameters), due to a synergistic effect on the central pathogenetic mechanisms of hypertension and obesity - insulin resistance and sympathetic overactivity.